1999
DOI: 10.1093/clipsy.6.4.462
|View full text |Cite
|
Sign up to set email alerts
|

The pursuit of consensus in psychotherapy research and practice.

Abstract: With the growing pressures from managed care and biological psychiatry to demonstrate the clinical effectiveness of psychosocial interventions, the field has attempted to arrive at a consensus about which treatments work for whom. Although it is essential for the practice of psychotherapy to have an empirical base, the issue is complicated by existing methodological constraints that can limit the clinical generalizability of our research findings. Within this context, this article comments on the role of thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Such skepticism may not be unreasonable given the lack of current research attention to the realities of the usual care practice context (e.g., the differences between the efficacy research treatment context and community‐based mental health clinics; Addis, Wade, & Hatgis, 1999; Burns et al., 1999; Hawley & Weisz, 2002; Hoagwood et al., 2001; Weisz et al., 1995; Weisz & Hawley, 1998). This skepticism may also partly reflect a long‐standing rift between researchers and clinicians, where clinicians feel disenfranchised by researchers, believing that research often disregards their realities and invalidates their experience as professionals (Abrahamson, 1999; Fensterheim & Raw, 1996; Goldfried, 1999; Norcross, 1999). Long implicit, this rift has become more explicit and openly debated recently, even in the lay media.…”
Section: Need For Hybrid Research On Children's Mental Health Carementioning
confidence: 99%
“…Such skepticism may not be unreasonable given the lack of current research attention to the realities of the usual care practice context (e.g., the differences between the efficacy research treatment context and community‐based mental health clinics; Addis, Wade, & Hatgis, 1999; Burns et al., 1999; Hawley & Weisz, 2002; Hoagwood et al., 2001; Weisz et al., 1995; Weisz & Hawley, 1998). This skepticism may also partly reflect a long‐standing rift between researchers and clinicians, where clinicians feel disenfranchised by researchers, believing that research often disregards their realities and invalidates their experience as professionals (Abrahamson, 1999; Fensterheim & Raw, 1996; Goldfried, 1999; Norcross, 1999). Long implicit, this rift has become more explicit and openly debated recently, even in the lay media.…”
Section: Need For Hybrid Research On Children's Mental Health Carementioning
confidence: 99%
“…For example, blue-ribbon panels commissioned to examine the state of mental health services in community settings have consistently concluded that clinicians delivering community mental health services demonstrate only limited knowledge of validated treatment approaches, and even when such professionals do become informed, they find such approaches neither feasible nor relevant to their treatment settings and population (National Advisory Mental Health Council, 1999). Widely known as the "researcher-practitioner gap" (Goldfried, 1999;Greenberg, 1994), this current disconnection between psychotherapy science and mental health services might inadvertently reflect the minimization of the therapist as a significant participant in psychotherapy research, as well as the epistemological disfavor shown nonmechanistic approaches that privilege the therapy relationship (Abrahamson, 1999;Bohart, O'Hara, and Leitner, 1998). Of additional concern is the fact that impact of overall treatment quality and appropriateness are infrequently examined at policy, program, and institutional levels (Magura, 2000;Magura, Schildhaus, Rosenblum, and Gastfried, 2002), and only limited work has been produced regarding how these interact with patients' geographical, cultural, and ethnic differences (Berlin, 2002;Snowden and Yamada, 2005).…”
Section: Clarkmentioning
confidence: 99%
“…75 Given the difficulties obtaining consensus even in the natural sciences, we must be scrupulous not to prematurely demand that clinicians should adhere to manuals not fully developed through all three stages. 58,59,76 Additionally, developing valid measures of competence is much easier said than done. 77,78 We also need to recognize and respect that good clinicians often combine different theoretical approaches to address the individual clinical situation.…”
Section: Palliative Care Manualized Communication Approaches Might Bementioning
confidence: 99%